Text Materialities, Affordances, and the Embodied Turn in the Study of Reading - Hillesund, Terje; Schilhab, Theresa; Mangen, Anne (Frontiers in Psychology, 2022)
Digital texts have for decades been a challenge for reading research, creating a range of questions about reading and a need for new theories and concepts. In this paper, we focus on materialities of texts and suggest an embodied, enacted, and extended approach to the research on digital reading. We refer to findings showing that cognitive activities in reading are grounded in bodily and social experiences, and we explore the cognitive role of the body in reading, claiming that – influenced by tacit knowledge and the task at hand - textual meaning is enacted through a mental and physical engagement with text. Further, applying the concept of affordances, we examine how digital technologies have induced new ways of physically handling and mentally interpreting text, indicating that brain, body, text, and technologies are integrated parts of an extended process of reading. The aim of the paper is to encourage empirical research on the interplay between body (including brain), text, and text materialities, a focus we argue will deepen our understand of the current transformation of reading.